2016
DOI: 10.1002/lt.24498
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation significantly improves global functioning and cerebral processing

Abstract: The functional basis of cognitive and quality of life (QOL) change after liver transplant is unclear. We aimed to evaluate the neuro-metabolic and functional brain changes as modulators of cognition and QOL post-transplant in cirrhotics with/without pre-transplant cognitive impairment and hepatic encephalopathy (HE). Cirrhotics underwent detailed cognitive and QOL assessment at enrollment and six months post-transplant. A subset underwent brain MRI [Functional (fMRI), diffusion tensor imaging (DTI) and spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…It is assumed that after OLT, HE‐associated cognitive dysfunction recovers. Ahluwalia et al showed an improvement of cognitive function and cerebral magnetic resonance spectroscopy from before OLT to 6 months after OLT in 66 patients of which 38 had a history of HE before OLT . However, 21% of the patients still showed cognitive impairment after OLT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is assumed that after OLT, HE‐associated cognitive dysfunction recovers. Ahluwalia et al showed an improvement of cognitive function and cerebral magnetic resonance spectroscopy from before OLT to 6 months after OLT in 66 patients of which 38 had a history of HE before OLT . However, 21% of the patients still showed cognitive impairment after OLT.…”
Section: Discussionmentioning
confidence: 98%
“…Ahluwalia et al showed an improvement of cognitive function and cerebral magnetic resonance spectroscopy from before OLT to 6 months after OLT in 66 patients of which 38 had a history of HE before OLT. (23) However, 21% of the patients still showed cognitive impairment after OLT. Campagna et al as well showed cognitive improvement 9-12 months after OLT in 65 patients of which 23 had a history of HE before OLT.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown OHE patients have a variable outcome post-transplant(22, 26). A recent study demonstrated that a simple pre-transplant OHE diagnosis was not a powerful predictor of post-transplant cognitive impairment on multi-modal MR imaging(27, 28). Therefore, the restoration of this learning ability points towards a hopeful illness course after transplant in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in an fMRI study examining the functional basis of cognitive change after liver transplantation Ahluwalia et al, found robust activation in areas within the dorsolateral prefrontal cortex and anterior cingulate cortex(27). These brain regions are hypothesized to underlie successful Stroop test performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation